AB1181 Anti-ro60 seropositivity determines epitope specificity of anti-ro52 antibodies in patients with autoimmune rheumatic and malignant diseases. (12th June 2018) - Gkoutzourelas, A.; Liaskos, C.; Papadopoulos, V.; Mytilinaiou, M.G.; Christina, K.; Scheper, T.; Meyer, W.; Bogdanos, D.P.; Papandreou, C.; Sakkas, L.I.
Abstract : Background: Epitope mapping of anti-Ro52 antibodies (abs) has been extensively studied in patients with Sjögren's syndrome (SjS) and systemic lupus erythematosus (SLE). Comprehensive epitope mapping in systemic sclerosis (SSc) or malignant diseases (MD), also associated with anti-Ro52 abs, has not been performed. Objectives: To fully characterise Ro52 epitopes in anti-Ro52 ab-positive SSc and MDs. Methods: Testing was performed in sera from 95 anti-Ro52 positive patients with various autoimmune diseases (32 SSc, 20 SjS, 28 SLE) and 15 with malignant diseases (MD). Five recombinant Ro52 fragments [Ro52–1 (aa 1–127), Ro52–2 (aa 125–268), Ro52–3 (aa 268–475), Ro52–4 (aa 57–180, partly overlapping Ro52–1 and Ro52–2), and Ro52–5 (aa 181–320, partly overlapping Ro52–2 and Ro52–3)] were tested by line-immunoassay. Anti-Ro60 was tested by ELISA. Results: Overall, reactivity to Ro52–1, Ro52–2, Ro52–3, Ro52–4 and Ro52–5 were present in 35.8%, 100%, 0%, 32.6%, 50.5%, respectively. Patients with SLE more frequently recognised Ro52–1, Ro52–4 and Ro52–5 than patients with SSc and malignant diseases. When epitope mapping was analysed in accordance to Ro60 reactivity, patients where subdivided in 50 Ro52pos/Ro60pos (13 patients with SSc, 14 with SjS, 18 with SLE and 5 patients with MD) and 45 Ro52pos/Ro60neg patients (19 with SSc, 6 with SjS, 10 with SLE and 10 patients with MD) and the following findings were noted: Abs to Ro52–1 were present in 26/50 (52%) Ro52pos/Ro60pos compared to 8/45 (18%) Ro52pos/Ro60neg patients (p<0.001); antibodies to Ro52–2 were present in all patients; antibodies to Ro52–3 was totally absent; antibodies to Ro52–4 were present in 23/50 (46%) Ro52pos/Ro60pos compared to 8/45 (18%) Ro52pos/Ro60neg patients (p=0.003); antibodies to Ro52–5 were present in 33/50 (66%) Ro52pos/Ro60pos compared to 15/45 (33.3%) Ro52pos/Ro60neg patients (p=0.001). Ro52 epitope recognition did not differ between Ro52pos/Ro60pos and Ro52pos/Ro60neg in patients with SLE, SjS and patients with MD. In SSc anti-Ro52–1 reactivity was present in 8/13 (62%) Ro52pos/Ro60pos compared to 0/19 (0%) Ro52pos/Ro60neg patients (p<0.001); In SSc, anti-Ro52–5 reactivity was present in 9/13 (69.2%) Ro52pos/Ro60pos and 5/19 (26.3%) Ro52pos/Ro60neg patients (p=0.029). Ro52 epitope recognition in Ro52pos/Ro60pos patients did not differ amongst diseases. Conclusions: Ro52–1 (aa 1–127) and Ro52–4, partially overlapping with Ro52–1, (aa 57–180) are dominant epitopes in Ro52pos/Ro60pos patients but not in Ro52pos/Ro60neg patients with autoimmune rheumatic diseases, suggesting that amino acids 57–127 may contain an epitope specifically recognised by the Ro52pos/Ro60pos group. Whether Ro60 is responsible for the unmasking of Ro52 (aa57–127) neoepitope remains to be investigated. Disclosure of Interest: A. Gkoutzourelas: None declared, C. Liaskos: None declared, V. Papadopoulos: None declared, M. Mytilinaiou: None declared, K. Christina: None declared, T. Scheper Employee of: EUROIMMUN, W. Meyer Employee of: EUROIMMUN, D. Bogdanos: None declared, C. Papandreou: None declared, L. Sakkas: None declared